Tethys App Store: Simplifying deployment of web applications for the international GEOGloWS initiative. (December 2021) - Khattar, Rohit; Hales, Riley; Ames, Daniel P.; Nelson, E. James; Jones, Norman L.; Williams, Gustavious
Abstract: Portability of web applications between web servers of different organizations can be challenging and can complicate sharing and collaborative use of such tools. Given the distributed nature of the web, this lack of portability is usually not a concern because a user in one organization can link to and use a web application hosted by another organization. However, access control or differentiation may be needed by an organization in terms of area of interest, input data, analytical techniques, access control, presentation, branding, and language. This is true for many government organizations, and their associated web sites, and servers. In such cases, there are compelling political, branding, security, and privacy motivations that require each organization or agency to host and manage web applications on their own servers rather than using third party web sites over which they have little or no control. We present the design, development, and testing of a system for discovering, installing, and configuring environmental analysis web applications on localized web servers. The system works with applications developed using Tethys Platform, which is an open-source software stack for creating geospatially enabled web-based applications. The developed Tethys App Store includes a Tethys application user interface that allows a server manager to retrieve applications from the central repository and install them on a local server with relative simplicity, similar to the installation of a mobile application to a mobile device from a mobile application store. The system was developed to support deployment of water and environmental analysis web apps for the international Group on Earth Observations (GEO) Global Water Sustainability (GEOGloWS) initiative of the National Aeronautics and Space Administration (NASA) and several partner organizations. Revised Highlights: We present the design and development of an app store for Tethys Platform based water resources web applications. The developed system combines Conda packaging system and GitHub actions as a build system. It represents a web application distribution methodology of building, sharing, and deploying to various hardware systems. It was tested by deploying web portals for partners of the Group on Earth Observations Water Sustainability initiative.